Responses from Incubators to the Creative Economy - Zardo, Julia; Mello, Ruth (Brazilian Journal of Operations & Production Management, 2018)
The article analyzes the creative economy and how incubators around the world are managing to meet its needs. We chose as case studies the top 13 best incubators in the world according to UBI Index 2016 to demonstrate, again, the importance of the creative economy and corresponding responses from incubators. We focus especially on the case of the Genesis Institute, in Brazil which had to modernize itself to adapt to the emerging creative economy. From the research conducted, the following conclusions are reached: one, creative sectors are growing; and, two, it is necessary for incubators to adapt and meet these sectors’ needs not only in Brazil but globally. Furthermore, it is possible to notice that certain incubators which have not developed creative sectors extensively will soon need to modernize, as their countries are already recognizing the importance of creative economy. Considering the incubators analyzed by this article and which have adapted to the emerging creative economy and its needs, it is considered that modernization is necessary to effectively serve startups.